2019
DOI: 10.1128/jvi.00233-19
|View full text |Cite
|
Sign up to set email alerts
|

Specific ActivationIn Vivoof HIV-1 by a Bromodomain Inhibitor from Monocytic Cells in Humanized Mice under Antiretroviral Therapy

Abstract: Combination antiretroviral therapy (cART) effectively suppresses HIV-1 replication and enables HIV‑infected individuals to live long, productive lives. However, the persistence of HIV-1 reservoirs of both T and myeloid cells with latent or low-replicating HIV-1 in patients under cART makes HIV-1 infection an incurable disease. Recent studies have focused on the development of strategies to activate and purge these reservoirs. Bromodomain and extraterminal domain proteins (BETs) are epigenetic readers involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…Additionally, bromodomain and extraterminal domain inhibitors (BETi) are epigenetic regulators that affect HIV-1 replication by preventing positive transcription elongation factor b (P-TEFb) from interacting with BRD4, thereby allowing Tat to bind P-TEFb and mediating HIV-1 transcriptional elongation. 63 , 64 Although molecules in this class have been evaluated only preclinically for HIV-1 latency reversal, 65 different BETis are being investigated in clinical trials as cancer therapeutics. 66 Because we find that Smac mimetics can strongly synergize with a variety of epigenetic regulators, combinations of Smac mimetics with both HDACi and BETi represent potential opportunities to deliver increased latency reversal activity, while minimizing toxicities due to reduced doses of the individual drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bromodomain and extraterminal domain inhibitors (BETi) are epigenetic regulators that affect HIV-1 replication by preventing positive transcription elongation factor b (P-TEFb) from interacting with BRD4, thereby allowing Tat to bind P-TEFb and mediating HIV-1 transcriptional elongation. 63 , 64 Although molecules in this class have been evaluated only preclinically for HIV-1 latency reversal, 65 different BETis are being investigated in clinical trials as cancer therapeutics. 66 Because we find that Smac mimetics can strongly synergize with a variety of epigenetic regulators, combinations of Smac mimetics with both HDACi and BETi represent potential opportunities to deliver increased latency reversal activity, while minimizing toxicities due to reduced doses of the individual drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, it was more recently shown that JQ1 induces dissociation of BRD4 from the repressive chromatin remodeling proteins (SWI/SNF) at the HIV LTR, thereby reversing BRD4-mediated HIV transcriptional suppression [23]. This is considered to be independent of Tat-mediated transcription elongation In addition to JQ1, several other BET inhibitors have been tested in HIV infection models with some compounds demonstrating HIV latency-reversing activities, such as UMB-136 [39], MMQO [40], OTX015 [41], and I-BET151 [42]. Mechanistically, OTX015 increases the occupancy of CDK9 at the HIV-1 LTR and activates RNAP II CTD phosphorylation, hence reactivating HIV expression [41].…”
Section: Modulate Brd4 By Pan-bet Inhibitors (Beti) To Activate Hiv Tmentioning
confidence: 99%
“…BET inhibitors, including JQ1, MS417, I-Bet, and I-Bet151, have reactivated HIV from latency via the action of the positive transcription elongation factor b, a subject of acetylation, in a model of HIV latency (82,122). Furthermore, I-Bet151 was investigated in humanized mice treated with suppressive cART (81). In this case, I-Bet151 did not have any observed significant toxic effect on the treated mice, and nine days after I-Bet151 initiation, HIV-1 viremia rebounded and was associated with a higher HIV-1 RNA level in different organs.…”
Section: Bromodomain and Extra-terminal Domain Inhibitorsmentioning
confidence: 99%